Gender Identity Laws: The legal status of global sex/gender identity recognition - Ryan, John (2019)
Official identity is a powerful thing. More than just feelings, diagnosis, or behaviors, official identity marks the status by which one can gain, or lose, access to certain social rights, responsibilities, and privileges. It can be predicated on biology or on the “determination” of other social identities. And it can serve as the means by which other identities can be determined. The ability to alter one’s official identity is a key mechanism whereby one can essentially change who they are, and what they can become, in the eyes of the law. This paper will examine three principal types of global gender recognition identity laws—those that require official approval by “experts,” those that provide options for a third gender, and those that allow for self-declaration. Case studies will be examined of laws in the United Kingdom, Nepal, and Argentina respectively to demonstrate the potential benefits and shortcomings of each type of law. The conclusion will consider the potential ramifications of removing gender as an official identity marker entirely, a move now considered by some to be the end result or goal of many of these laws.